Financial Performance Analysis of The Depok City Health Department in 2020-2022 - Gayatri Pungky Handayani; Rida Prihatni; I Gusti Ketut Agung Ulupui (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to analyze the financial performance of the Depok City Health Office in the 2020-2022 period. Financial performance is analyzed using several methods, namely Value For Money, variance analysis, growth analysis, and expenditure compatibility analysis. This research utilizes secondary data from the Government Agency Performance Accountability Report (LAKIP) and Budget Realization Report (LRA) of the Depok City Health Office for three periods. The research method used is descriptive with a quantitative approach. Data were collected through documentation techniques. The results showed that the financial performance of the Depok City Health Office based on the Value for Money method during the 2020-2022 period was classified as economical. Efficiency and effectiveness ratios fluctuated, not reaching the efficient and effective level in 2020 and 2021, but reaching the efficient and effective category in 2022. The variance ratio shows fluctuating development with instability in revenue variance and consistently favorable expenditure variance performance. Based on the growth ratio, there is an overall positive trend in financial performance, although there are significant fluctuations in 2020-2021. The year 2022 shows a drastic improvement in both revenue growth and expenditure growth, indicating a significant improvement in financial performance. The expenditure harmony ratio showed fluctuating results but experienced a positive trend over the three periods in the management of operating and capital expenditures, evidenced by an increase in the budget utilization harmony category in 2022